Evolutionary history of ergot with a new infrageneric classification (Hypocreales: Clavicipitaceae: Claviceps) - Píchová, Kamila; Pažoutová, Sylvie; Kostovčík, Martin; Chudíčková, Milada; Stodůlková, Eva; Novák, Petr; Flieger, Miroslav; van der Linde, Elna; Kolařík, Miroslav (Molecular phylogenetics and evolution, 2018)
The ergot, genus Claviceps, comprises approximately 60 species of specialised ovarial grass parasites famous for the production of food toxins and pharmaceutics. Although the ergot has been known for centuries, its evolution have not been resolved yet. Our approach combining multilocus phylogeny, molecular dating and the study of ecological, morphological and metabolic features shows that Claviceps originated in South America in the Palaeocene on a common ancestor of BEP (subfamilies Bambusoideae, Ehrhartoideae, Pooideae) and PACMAD (subfamilies Panicoideae, Aristidoideae, Chloridoideae, Micrairoideae, Arundinoideae, Danthonioideae) grasses. Four clades described here as sections diverged during the Paleocene and Eocene. Since Claviceps are parasitic fungi with a close relationship with their host plants, their evolution is influenced by interactions with the new hosts, either by the spread to a new continent or the radiation of the host plants. Three of the sections possess very narrow host ranges and biogeographical distributions and have relatively low toxicity. On the contrary, the section Claviceps, comprising the rye ergot, C. purpurea, is unique in all aspects. Fungi in this section of North American origin have spread all over the world and infect grasses in all subfamilies as well as sedges, and it is the only section synthesising toxic ergopeptines and secalonic acids. The evolutionary success of the Claviceps section members can be explained by high toxin presence, serving as feeding deterrents and playing a role in their protective mutualism with host plants. Closely related taxa Neoclaviceps monostipa and Cepsiclava phalaridis were combined into the genus Aciculosporium.
Keywords: Host Specificity; Alkaloids; zeměpis; Ergot Alkaloids; Phylogeny; genetické lokusy; Geography; Ergochromes; Clavicipitaceae; sekundární metabolismus; časové faktory; Molecular dating; hostitelská specificita; Multilocus phylogeny; Jižní Amerika; námelové alkaloidy; fylogeneze; Bayesova věta; Claviceps; South America; Secondary Metabolism; Time Factors; Bayes Theorem; Genetic Loci; Host pathogens